Energy system contributions in upper and lower body wingate tests in highly trained athletes - Julio, U.; Panissa, V.; Cury, R.; Agostinho, M.; Esteves, J.; Franchini, E. (Research Quarterly for Exercise and Sport, 2019)
Purpose: This study compared the energy system contributions and relationship between mechanical and energy system variables in upper and lower body Wingate tests (WAnT) in judo athletes. Method: Eleven male judo athletes (18 ± 1 years, 174.3 ± 5.3 cm, 72.6 ± 9.9 kg, 11.8 ± 1.7% body fat) attended two laboratory sessions to perform two WAnT (upper and lower body) and two incremental tests (upper and lower body). The energy contributions of the oxidative, glycolytic, and phosphagen (ATP-PCr) systems were estimated based on oxygen consumption (VO2) during WAnT, delta of lactate, and the fast phase of excess VO2, respectively. Results: The upper and lower body presented similar results of oxidative (21 ± 4% vs 23 ± 3%) and ATP-PCr system contributions (29 ± 6% vs 32 ± 5%). The glycolytic system contribution (50 ± 5% vs 45 ± 4%) was higher in the upper body. The variance of mechanical variables in upper body was explained by glycolytic (R² = 0.49-0.62) and oxidative systems (R² = 0.44-0.49), whereas the variance of mechanical variables in lower body was explained by ATP-PCr (R² = 0.41-0.55) and glycolytic systems (R² = 0.62-0.94). Conclusions: During WAnT, the glycolytic system presented the major energy contribution, being higher in the upper body. Moreover, mechanical and energy system variables presented a distinct relationship when comparing upper and lower body WAnT.